The formation of highly stable form of isotactic polybutene-1 electrospun membrane via self-seeding. (21st September 2022) - Kashif, Muhammad; Li, Huihui; Rasul, Sadia; Athir, Naveed; Liu, Yong
Abstract: The non-isothermal crystallization behavior from the incomplete melting of isotactic polybutene-1 (iPB-1) electrospun (e-spun) membranes is investigated. The standard sample of e-spun iPB-1 contains the concomitant form II and I′, which are less stable than form I. So, we adopted a pathway of treating a nucleation stage of concomitant polymorphs. Cross-nucleation was observed when a stable polymorph nucleates and grows on a formerly existing polymorph. The present outcomes revealed that upon non-isothermal crystallization of a partially molten state, an appropriate Domain of self-seeding temperature ( Ts ) 115 °C to 125 °C directed towards forming highly stable iPB-1 form I. Such phenomena might be typified to the memory effect of their pristine crystalline structure and the inter-lamella confinement effect in that particular and constrained environment of the partially molten state. In addition, the influence of variable applied voltage on the self-nucleation mechanism was also considered comparatively. Based on their morphology, spectral, and thermal analysis, samples spun at 11 kV were relatively preeminent to proceed with the self-seeding route. Graphical abstract: Image 1 Highlights: Morphology of iPB-1 e-spun blend membranes was studied upon varying voltage. Self-seeding effect was performed on the samples spun at various voltages comparatively. By acting on a nucleation stage using partial melting, a highly stable form I can be achieved. The direct formation of form I present a novel prospective for commercial interesting polymer.